1973
DOI: 10.1063/1.1654823
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aluminum-titanium electrical contacts on silicon

Abstract: An aluminum-titanium metallization scheme for use in silicon integrated circuits is described. This metallization can produce high-conductance electrical contacts with negligible dissolutions of silicon. The desirable contact is lost, however, if a TiAl3 reaction product is allowed to consume the entire Ti layer. The TiAl3 forms during the postmetallization heat treatment used to stabilize the electrical characteristics of the contact. The Ti layer is found to be consumed in this reaction at a rate proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(45 citation statements)
references
References 5 publications
6
39
0
Order By: Relevance
“…3. According to [8,9] the intermetallic phase -Al Ti grows at the interface, with the diffusion coefficient following the Arrhenius equation with a frequency factor of D "0.15 cms\ and an activation energy of Q"1.85 eV. This interface layer can be clearly seen in the profile of Fig.…”
Section: Depth Profiling Of Minor Elementsmentioning
confidence: 83%
“…3. According to [8,9] the intermetallic phase -Al Ti grows at the interface, with the diffusion coefficient following the Arrhenius equation with a frequency factor of D "0.15 cms\ and an activation energy of Q"1.85 eV. This interface layer can be clearly seen in the profile of Fig.…”
Section: Depth Profiling Of Minor Elementsmentioning
confidence: 83%
“…It is reported that the compound TiAl 3 is formed at these temperatures [28], [30]. The reaction kinetic of TiAl 3 formation is empirically determined by Bower [30]. The amount of Ti consumed in the reaction with Al to form TiAl 3 increases proportionally to the square of heating time.…”
Section: Ti/al Stack Against Spikingmentioning
confidence: 99%
“…Since a contact formation annealing at 400 • C is used, we only consider Ti aluminides in this study. It is reported that the compound TiAl 3 is formed at these temperatures [28], [30]. The reaction kinetic of TiAl 3 formation is empirically determined by Bower [30].…”
Section: Ti/al Stack Against Spikingmentioning
confidence: 99%
“…The early stages of phase reaction between Ti and Al were characterised by the initial formation of TiAl 3 in both bulk and thin film samples for any composition and for temperature up to the melting point of Al [9][10][11][12][13][14]. The intermetallic phases, i.e., g-TiAl, a 2 -Ti 3 Al and TiAl 2 , were not observed in the early stages of the reaction.…”
Section: Introductionmentioning
confidence: 99%